In Search of Our Students’ Voices: The Student Focus Day Story - Robertson, Kenneth J. (LEARNing Landscapes, 2018)
Much of the literature on “student engagement” focuses on “motivating students to learn” (Voke, 2002), but what of our students’ voices in the context of board-wide planning for their success? This is the story of the New Frontiers School Board’s Student Focus Day, an initiative aimed at opening the planning process to the voices of our students by inspiring them to engage in open conversation, share in the leadership, and take responsibility for enacting the changes they envision.